Enhancing academic achievement and artistic appreciation in music students through inquiry and task-based learning: An experimental study - Zhang, Meng; Attapaiboon, Tinnakorn; Jantharajit, Nirat (Asian Journal of Contemporary Education, 2025)
This study examines the effectiveness of a blended instructional approach combining Inquiry-Based Learning (IBL) and Task-Based Learning (TBL) in enhancing academic achievement and artistic appreciation among music performance students. Methodology: Fifty second-year students from Beijing City College participated divided into an experimental group using the blended instructional approach and a control group following traditional teaching methods. The intervention lasted two months and its impact was evaluated through pre- and post-intervention comparisons of academic achievement and artistic appreciation. Findings: Results revealed significant improvements in the experimental group with mean academic achievement increasing from 115.12 ± 4.53 to 117.56 ± 4.16 (P<0.05) and mean artistic appreciation rising from 75.24 ± 3.40 to 76.84 ± 3.91 (P<0.05). Additionally, the experimental group outperformed the control group in academic achievement (t=-6.866, Cohen’s d=1.373) and artistic appreciation (t=-7.333, Cohen’s d=1.467). Practical Implications: These findings suggest that integrating IBL and TBL provides a robust framework for improving cognitive and artistic outcomes in music education, offering teachers an effective alternative to traditional teaching methods.